APLIKASI ANIMASI INTERAKTIF EDUKASI PENGENALAN KESEHATAN MENTAL: Interactive Animated Educational Application For The Introduction Of Mental Health - Fatma, Fatmawati Hasim; T.G. Kaunang, Sumenge; V. Akay, Yuri (Universitas Sam Ratulangi, 2024)
Abstract— Mental health is a very important factor in achieving overall health. However, when compared with infectious diseases, mental health problems still really need attention. According to the Chair of the Association of Indonesian Mental Medicine Specialists (PDSKJI), Dr. Eka Viora, SpKJ, noted that 15.6 million Indonesians experience depression and there is still a lack of understanding among Indonesians about mental disorders (Datik Health, 2019). With the times, technological development is very rapid, as various types of technology emerge that can be used as educational media such as games by making quizzes a challenge that must be solved. This research aims to develop an educational game introducing mental health, a 3D game using the Multimedia Development Life Cycle (MDLC) development methodology. And developed using the Unity game engine software. Based on the results of the feedback test (questionnaire), a positive response was seen that began with a greater appreciation for a number of factors, including the desire for interactive animation educational learning about metal health, effective delivery of material, intuitive interest in learning more about metal health, and power pull the gamei by accident. Key words— Game Development; Labyrinth; Mental health; Multimedia Development Life Cycle. Abstrak— Kesehatan mental adalah faktor yang sangat penting dalam mencapai kesehatan secara keseluruhan. Tetapi jika dibandingkan dengan penyakit menular masalah kesehatan mental masih sangat perlu diperhatikan. Menurut Ketua Perhimpunan Dokter Spesialis Kedokteran Jiwa Indonesia (PDSKJI), dr Eka Viora, SpKJ, mencatat 15,6 juta penduduk Indonesia mengalami depresi dan masih kurangnya pemahaman masyarakat Indonesia tentang gangguan jiwa (Detik Health, 2019). Dengan perkembangan zaman, pengembangan teknologi sangatlah pesat, seperti halnya bermunculan berbagai jenis teknologi yang dapat dimanfaatkan sebagai sarana media edukasi seperti game dengan menjadikan quiz sebagai tantangan yang harus dipecahkan. Penelitian ini bertujuan mengembangangkan game edukasi pengenalan kesehatan mental, game berbentuk 3D dengan menggunakan Metodologi pengembangan Multimedia Development Life Cycle (MDLC). Dan dikembangkan menggunakan software game engine unity. Berdasarkan hasil uji coba uimpan balik (kuesioner), terlihat tanggapan positif yang diawali dengan apresiasi yang lebih besar terhadap sejumlah faktor, antara lain pengenalan pendidikan animasi interaktif kesehatan mental, penyampaian materi yang efektif, minat pengguna untuk mempelajari lebih lanjut tentang kesehatan mental, dan daya tarik game secara keseluruhan. Kata Kunci— Kesehatan mental; Labirin; Multimedia Development Life Cycle; Pengembangan Game